Factors Influencing The Incidence Of Cervical Cancer In Patients At Adam Malik Hospital - Simarmata, Mesrida; Panjaitan , Elvina (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Cancer cervix is disturbance growth mobile And is a group of diseases characterized by failure to control cell proliferation and maturation in cervical tissue . Asia Southeast occupies ranking fifth amount number incident And death the highest, namely 1.91% and 1.16% of people . Objective: to m analyzing Risk Factors Affecting the Occurrence of Cervical Cancer at the H. Adam Malik Central General Hospital, North Sumatra Province in 2024 Method : This type of research is descriptive analytical. with design study Cross Sectional . The population is all those who have cervical cancer at H Adam Malik Hospital. A total of 42 people with a total sampling technique of 42 people. Results : The age of the respondents is mostly 35-45 years old, 25 people (60%), the majority of high school education is 21 people (51%), the majority of injections are 19 people (45%), the majority of cancer stage 2 is 21 people (50%). From the analysis of the chi square test of age with the stage of cervical cancer incidence, the results of the p value p = 0.571 and the results of the square test of contraceptive use with the incidence of cervical cancer p value = 0.401 that there is no relationship between age and contraceptive use with the stage of cancer . Conclusion : Factors that influence the occurrence of cervical cancer at Adam Malik Hospital in 2024 are age >35 years, high school education, users of injectable contraceptives, stage 2, there is no relationship between age and contraceptives with the stage of cervical cancer. Suggestion: It is recommended to do early detection through the IVA test as early as possible so that the incidence of cervical cancer can be overcome earlier